Do pandiabolismo intertextual de Joel-Peter Witkin - Campos, Israel Souto (2012)
In an attempt to approach the concept of pandiabolism created by Wolfgang Kayser, this study is on hold intertextual analysis of wealth that five decades of work, they documented in the book The Bone House, offering as an object. The research takes as methodology the intertextual analysis of Witkin’s images through criticism of his creative processes. As subsidy theory, it employed the interdisciplinary dialogue, presented by Lucy Figueiredo, as a tool to this cartography.